Celebrating the bond between children and nature: designing a sensory outdoor learning environment for Garfield Elementary School in Augusta, Kansas - Christner, Cammie (Kansas State University, 2013)
The current educational model utilized in the United States focuses on teaching technology, preparing for standardized tests, and training students to be productive members of society. These are all valuable and necessary educational goals, especially considering the fact that the current national trend is to promote citizens’ integration into a more global community and job market—significantly affecting the work opportunities available to our country’s youths. However, one of the most necessary and fundamental aspects of childhood—outdoor learning in nature—is being undervalued. Outdoor learning experiences in the natural environment are exceptionally important in encouraging holistic childhood development because they offer children firsthand experiences with natural processes. Through interactions with nature, children are able to witness the impact that human actions have upon the environment. As Richard Louv asserts in the Last Child in the Woods, “Healing the broken bond between our young and nature—is in our self-interest, not only because aesthetics or justice demands it, but also because our mental, physical, and spiritual health depends upon it” (Louv, 2008, 3). The broken relationship between America’s youths and nature must be healed. Public schools offer a unique opportunity for children to be reacquainted with nature because about 90% of American students below the college level attend public schools. In the year 2009, over 2.3 million students attended public elementary schools; 226,082 of those students were in Kansas (National Center for Education Statistics, 2012). Garfield Elementary School in Augusta, Kansas is an ideal situation for the development of an outdoor learning environment that promotes student awareness and connection to local nature. The nature-oriented design of Garfield Elementary School’s grounds, described in this Master’s Report, fosters the creation of deep-seeded emotional ties to the natural world in the children who experience the site—effectively combating Nature-Deficit Disorder by encouraging students to become environmental stewards. This is accomplished by using children’s literature to inspire the organization of spatial environment variety and a range of natural elements (such as water) on the school site, which encourage students to engage in five outdoor learning activities: physical, creative, sensorial, solitary and social.
Keywords: Children; Nature; Literature; Design; Playground; Developmental Psychology (0620); Early Childhood Education (0518); Landscape Architecture (0390)